2009
DOI: 10.1002/jmri.21861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shot number on the calculated apparent diffusion coefficient in phantoms and in human liver in diffusion‐weighted echo‐planar imaging

Abstract: Purpose:To show the signal intensity varies with shot number in diffusion-weighted (DW) echo-planar imaging (EPI) and affects apparent diffusion coefficient (ADC) calculation. Materials and Methods:This prospective study was performed on 35 adult patients and 20 volunteers. Measurements were made on a 3T scanner using a breathhold DW spin-echo EPI (SE EPI) sequence. Three protocols were used: A) eight consecutive shots at a fixed b-value of 0 seconds/mm 2 with TR ϭ 1000 and 3000 msec; B) seven consecutive shot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Most other investigators have attempted to determine an ADC threshold that can be used to differentiate benign and malignant lesions. However, the ADC value of normal liver is variable and is effected by the b values used, the acquisition technique (respiratory triggered, vs. free breathing vs. breath hold), shot number, pulse triggering, the anatomical location, portal venous blood flow related to post‐prandial state, artefacts and hepatic fibrosis . These factors make the application of a single ADC threshold for characterisation unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…Most other investigators have attempted to determine an ADC threshold that can be used to differentiate benign and malignant lesions. However, the ADC value of normal liver is variable and is effected by the b values used, the acquisition technique (respiratory triggered, vs. free breathing vs. breath hold), shot number, pulse triggering, the anatomical location, portal venous blood flow related to post‐prandial state, artefacts and hepatic fibrosis . These factors make the application of a single ADC threshold for characterisation unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…When considering causal effects of ADC differences between sequences, it is important to consider the impact of the sequence parameters. In a study of 35 patients and 20 volunteers, Shiehmorteza et al (30), reported that shot number in a SE EPI sequence may influence ADC, such that the application of a “dummy” b = 0 scan or scans may need to be acquired to attain a steady‐state before further DWI acquisitions. Our data were acquired at 1.5T, whereas the data from Shiehmorteza et al, (30) were acquired at 3T with its concomitant higher T1 and greater difference between fully relaxed signals and steady‐state signals.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 35 patients and 20 volunteers, Shiehmorteza et al (30), reported that shot number in a SE EPI sequence may influence ADC, such that the application of a “dummy” b = 0 scan or scans may need to be acquired to attain a steady‐state before further DWI acquisitions. Our data were acquired at 1.5T, whereas the data from Shiehmorteza et al, (30) were acquired at 3T with its concomitant higher T1 and greater difference between fully relaxed signals and steady‐state signals. Also, our data were acquired with three signal averages and one dummy scan (BH) or six signal averages (FB) compared with their single acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Breathhold DW images were obtained using a customized DW spin-echo echo-planar-imaging (SE EPI) sequence (14). A pair of trapezoidal gradient pulses was applied along a single diffusion direction, which was the vector sum of the three physical gradients.…”
Section: Mri Sequencesmentioning
confidence: 99%